Identification of Biomarkers for Defense Response to Plasmopara viticola in a Resistant Grape Variety - Chitarrini, Giulia; Soini, Evelyn; Riccadonna, Samantha; Franceschi, Pietro; Zulini, Luca; Masuero, Domenico; Vecchione, Antonella; Stefanini, Marco; Di Gaspero, Gabriele; Mattivi, Fulvio; Vrhovsek, Urska (Frontiers in Plant Science, 2017)
Downy mildew (Plasmopara viticola) is one of the most destructive diseases of the cultivated species Vitis vinifera. The use of resistant varieties, originally derived from backcrosses of North American Vitis spp., is a promising solution to reduce disease damage in the vineyards. To shed light on the type and the timing of pathogen-triggered resistance, this work aimed at discovering biomarkers for the defense response in the resistant variety Bianca, using leaf discs after infection with a suspension of P. viticola. We investigated primary and secondary metabolism at 12, 24, 48 and 96 hours post inoculation (hpi). We used methods of identification and quantification for lipids (LC-MS/MS), phenols (LC-MS/MS), primary compounds (GC-MS), and semi-quantification for volatile compounds (GC-MS). We were able to identify and quantify or semi-quantify 176 metabolites among which 53 were modulated in response to pathogen infection. The earliest changes occurred in primary metabolism at 24-48 hpi and involved lipid compounds, specifically unsaturated fatty acid and ceramide; amino acids, in particular proline; and some acids and sugars. At 48 hpi, we also found changes in volatile compounds and accumulation of benzaldehyde, a promoter of salicylic acid-mediated defense. Secondary metabolism was strongly induced only at later stages. The classes of compounds that increased at 96 hpi included phenylpropanoids, flavonols, stilbenes and stilbenoids. Among stilbenoids we found an accumulation of ampelopsin H+vaticanol C, pallidol, ampelopsin D +quadrangularin A, Z-miyabenol C and α-viniferin in inoculated samples. Some of these compounds are known as phytoalexins, while others are novel biomarkers for the defense response in Bianca. This work highlighted some important aspects of the host response to P. viticola in a commercial variety under controlled conditions, providing biomarkers for a better understanding of the mechanism of plant defense and a potential application in field studies of resistant varieties.